Criminal Law Policy in Election Criminal Act Enforcement - Wilman Supondho Akbar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The regulation of election crimes in the Pilkada Law and the Election Law, especially in terms of the definition and mechanism for handling election crimes, has juridical implications, both formal and material. In terms of the definition of election crime, the emergence of the classification of election crimes and violations, does not necessarily emphasize the difference between the regulation of offenses and sanctions between crimes and violations, so that there tends to be over-criminalization in terms of criminal law enforcement. On the other hand, the mechanism for handling election crimes is limited by the time of handling, making many cases of alleged election crimes unfinished. In this context, the urgency of classifying election crimes into crimes and violations as well as establishing a mechanism for handling election crimes must be seen and measured from the perspective of criminal law policies. This study uses a normative law research approach, namely normative case studies in the form of products of legal behavior, in this case the legal products studied are the Pilkada Law and the Election Law. The research specification in this article is descriptive analytical research, which describes the applicable laws and regulations associated with legal theories and practices of implementing positive law concerning the enforcement of criminal law for election crimes in the perspective of criminal law policies. Based on the results of the study, the classification of election crimes into violations and crimes at the formulation level does not have clear boundaries and standards both qualitatively and quantitatively. This causes at the level of implementation and execution, the distinction between violations and crimes is no longer important. Thus, the classification of election crimes into violations and crimes does not have significant implications for law enforcement efforts for election crimes. In addition, the mechanism for handling election crimes regulated in the Pilkada Law and the Election Law is not able to maximally encourage the fulfillment of the legal objectives of law enforcement regulations in the Pilkada Law and the Election Law.